2020
DOI: 10.2147/nss.s270045
|View full text |Cite
|
Sign up to set email alerts
|

<p>Objective Short Sleep Duration is Related to the Peripheral Inflammasome Dysregulation in Patients with Chronic Insomnia</p>

Abstract: Objective: Insomnia with objective short sleep duration (IOSSD) is associated with an increased risk of cardiovascular morbidity, diabetes, neurocognitive impairment, and mortality. Inflammation is believed to be one of the main links between IOSSD and these diseases. The role of nucleotide-binding domain and leucine-rich repeat protein-3 (NLRP3) inflammasome in inducing activation of inflammatory signaling in IOSSD is not clear. In this study, we investigated the expression of NLRP3 inflammasome in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Sleep disturbances as well as short sleep duration have been associated with elevated inflammatory markers [100]. In patients with insomnia, the presence of short sleep, sleep fragmentation, and reduced slow-wave sleep were associated with higher inflammasome levels [101]. Sleep loss has also been shown to impact neuroinflammation and microglia.…”
Section: Sleep Affects Inflammatory and Neuroinflammatory Processesmentioning
confidence: 99%
“…Sleep disturbances as well as short sleep duration have been associated with elevated inflammatory markers [100]. In patients with insomnia, the presence of short sleep, sleep fragmentation, and reduced slow-wave sleep were associated with higher inflammasome levels [101]. Sleep loss has also been shown to impact neuroinflammation and microglia.…”
Section: Sleep Affects Inflammatory and Neuroinflammatory Processesmentioning
confidence: 99%
“…A previous study demonstrated the activation of NLRP3 inflammasome in IOSSD patients and proposed that changes in epinephrine and norepinephrine levels in patients may be partly responsible for NLRP3 inflammasome activation via stimulation of leukocyte adrenergic receptors [e.g., Adrenoceptor Beta 2 (ADBR2) and Toll-like-receptor-4 (TLR-4)] and activation of NF-κB-mediated inflammatory signal pathway. In addition, studies have discovered that NLRP3 activity is positively related to short sleep duration and sleep fragmentation ( Wang, 2020 ). In chronic insomnia patients, there is controversy in the findings that show the existence of a link between activation of NLRP3 inflammasome pathway and REM sleep duration ( Wang et al, 2020 ; Aghelan et al, 2022 ).…”
Section: Insomnia and Nlrp3 Inflammasomementioning
confidence: 99%
“…In addition, studies have discovered that NLRP3 activity is positively related to short sleep duration and sleep fragmentation ( Wang, 2020 ). In chronic insomnia patients, there is controversy in the findings that show the existence of a link between activation of NLRP3 inflammasome pathway and REM sleep duration ( Wang et al, 2020 ; Aghelan et al, 2022 ).…”
Section: Insomnia and Nlrp3 Inflammasomementioning
confidence: 99%
See 2 more Smart Citations